Efficacy and safety of lurasidone in schizophrenia: pooled analysis of European results from double-blind, placebo-controlled 6-week studies. (9th March 2022) - Calisti, Fabrizio; Cattaneo, Agnese; Calabrese, Mariangela; Mao, Yongcai; Tocco, Michael; Pikalov, Andrei; Goldman, Robert
Abstract : The objective of this study is to confirm the efficacy and safety of lurasidone in the acute treatment of schizophrenia in European patients. Data were pooled from three studies of patients randomized to 6 weeks of double-blind, placebo-controlled, fixed-dose (40/80 mg and 120/160 mg) lurasidone. The primary efficacy endpoint was a week 6 change in the Positive and Negative Syndrome Scale (PANSS) total score and secondary endpoints included the Clinical Global Impression, Severity scale (CGI-S). In total 328 safety patients were enrolled; 72.6% were completers. Endpoint change was significantly greater in patients treated with 40–80 mg/d and 120–160 mg/d compared to placebo on the PANSS total score ( P < 0.001) and the CGI-Severity score ( P < 0.001) for all comparisons. For PANSS total scores, endpoint effect sizes for lurasidone 40–80 mg/d and 120–160 mg/d were 0.68 to 0.77, respectively. Adverse events with a frequency ≥5% (and were greater than for combined lurasidone) were insomnia (11.7%), akathisia (11.3%), headache (7.4%), Parkinsonism (6.5%) and nausea (5.7%). Median changes (in mg/dL) at endpoint were minimal for total cholesterol (−8.0); triglycerides (−8.5) and glucose (−2.0) and in mean weight (−0.2 kg). In European patients with schizophrenia, short-term treatment with lurasidone in doses of 40–160 mg/d was generally safe, well-tolerated and effective with minimal effects on weight and metabolic parameters.